2008
DOI: 10.2332/allergolint.o-07-493
|View full text |Cite
|
Sign up to set email alerts
|

Plasma UGRP1 Levels Associate with Promoter G-112A Polymorphism and the Severity of Asthma

Abstract: The ELISA system for quantifying UGRP1 protein was established, and plasma UGRP1 levels were associated with the G-112A UGRP1 gene promoter polymorphism and the severity of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…We observed reduced levels of serum UGRP1 in carriers homozygous for A/A, which is consistent with the results of other studies that found association between the carriage of the SCGB3A2 −112A variant and lower levels of either SCGB3A2 expression (Niimi et al 2002, Song et al 2009 or serum UGRP1 (Inoue et al 2008). A guanine-to-adenine substitution at position −112 of the SCGB3A2 promoter disrupts the sequence of the binding site for CCAAT/ enhancer-binding protein α (C/EBPα), a positive regulator of the transcription of SCGB3A2 Song et al 2009).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…We observed reduced levels of serum UGRP1 in carriers homozygous for A/A, which is consistent with the results of other studies that found association between the carriage of the SCGB3A2 −112A variant and lower levels of either SCGB3A2 expression (Niimi et al 2002, Song et al 2009 or serum UGRP1 (Inoue et al 2008). A guanine-to-adenine substitution at position −112 of the SCGB3A2 promoter disrupts the sequence of the binding site for CCAAT/ enhancer-binding protein α (C/EBPα), a positive regulator of the transcription of SCGB3A2 Song et al 2009).…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, Inoue et al (2008) found elevated concentrations of this protein in mild asthma but two-fold decreased UGRP1 levels in severe asthma in comparison with the controls. In the murine model of allergic airway inflammation, UGRP1 was reported to inhibit lung inflammation (Chiba et al 2006).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, we do not know whether endogenous SCGB3A2 regulates pulmonary inflammation and/or fibrosis. However, the following evidence suggests a role for SCGB3A2 in inflammation in lung in vivo; in the ovalbumin-induced allergic airway inflammation model mouse, SCGB3A2 expression is reduced in the airways (24,48,49), and the plasma SCGB3A2 levels are significantly lower in severe asthmatics without oral corticosteroid treatment as compared with mild-or moderate-asthma patients and controls (50). In the current study, a rather strong focal SCGB3A2 expression was found in a part of epithelial cells, and overexpressed SCGB3A2 was accumulated in fibrotic foci of lungs of mice subjected to BLM.…”
Section: Discussionmentioning
confidence: 99%